Correspondence of Austronesian Phonemes in Jambi Malay Language: A Comparative Study of Seberang Jambi Sub dialect and Bungo Malay Sub dialect - Oktariza, Dodi (Jurnal Ilmiah Langue and Parole, 2021)
This research is aimed at: 1) describing the sound correspondence set of two sub dialects; 2) describing kinds of proto phonemes pattern in Jambi Malay sub dialect and Bungo Malay sub dialect. There are three steps conducted in the research, they are collecting data, analyzing data, and presenting the result of analysis. In collecting data, the writer used observational method by applying the elicitation technique, which is continued by several techniques, i. e facing conversation, taking note, and recording technique. In analyzing data, the writer also used qualitative and quantitative approaches. Qualitative approach is used in order to show the sound correspondence between two sub dialects. Then, the comparative method is used to compare and determine the inheritance pattern toward two sub dialects.The result of analysis are: 1) there are two of sound correspondences rules that mostly found in ultima and penultima position. namel r ~ R /- η # /and ə ~ ə /# b – In addition, inherited linearly, inherited with changes, and linearly with lost. The linearly inherited can be seen from some vocal of protolanguage, /*i/, /*a/, /*ə/ also consonant /*b/, /*l/, /*m/, /*p/, /*g/, /*s/, /*η/, /*k/, /*h/. Furthermore, dealing with Proto Austronesia language, it is also found that some proto phonemes are showing the alteration, namely innovation.